Need for long-term care depends on social standing - Johannes Geyer; Peter W. de Haan; Hannes Kröger; Maximilian Schaller (DIW Weekly Report, 2021)
The poor have a significantly shorter life expectancy than the wealthy. Using data from the Socio-Economic Panel, this Weekly Report shows that poorer people become in need of care earlier in life and more often. In addition, blue-collar workers have a higher risk of requiring care than civil servants, as do people with high job strain compared to those with low job strain. The risk of dependence on care is determined by society, income, and work. Therefore, socio-political reforms are needed to reduce this inequality, as it is only partially compensated for by the existing social security systems. To reduce the risk preventatively, a sustainable policy must begin during the employment phase and reduce strain then. To reduce the inequality in the short term, private co-payments should be decreased and made more dependent on disposable income. Abolishing the private system in favor of a single-payer health care system covering all residents would be effective as well, as those with private care insurance have a considerably lower risk of dependence on care.
Keywords: I10; I14; 330; SOEP; Long-term care; Inequality